Sistem Pendukung Keputusan Pemilihan Pegawai Non-PNS Terbaik Kantor Kepala Desa Menerapkan Metode MOORA dan ROC - Manurung, Siti Rugun; Prayuda, Iqbal (BEES: Bulletin of Electrical and Electronics Engineering, 2023)
Civil Servant (PNS) is a person who is a member of a government institution to provide services to the public and is appointed permanently and gets a position in office while a Non Civil Servant Government Employee (PPNPN) is an employee who is elected by an official in the agency to carry out tasks certain employees in these agencies as well as honorary employees listed in the BKN database who work in government agencies for a maximum of 5 years of service. In this study, the authors are interested in using 2 methods, namely the MOORA method and the ROC method as weighting, where these two methods are very suitable to be combined so as to get the best alternative and calculate all the tricks that really support decision making, in order to simplify the processing steps. So get the best alternative M7 with a value of 0.446 with the name Reza Siagian